Politik Etis Pemerintah Kolonial Hindia Belanda dan Pengaruhnya terhadap Pesantren - M. Syarif, M. Syarif (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2019)
This paper discusses about the influence of Dutch Colonial government policy in the framework of its Ethical Policy towards pesantren. The Ethical Policy carried out by the Dutch East Indies colonial government throughout the period of 1900 until the independence of Indonesia was accompanied by the issuance of a series of policies which were considered to be pressing and detrimental to Islamic education, especially pesantren in Indonesia, in the form of teacher ordinances, wild school ordinances, and the establishment of Dutch Schools which -since the beginning of the 20th century- the existence of these schools has a direct influence on the existence of Islamic Education, especially pesantren. The effect of this policies was the transfer of pesantren to the rural areas just to maintain their characteristics accompanied by their resistance to infiltration of foreign cultures presented by the Dutch through Western-style public schools and The birth of the madrasah as a response to demands for changes in the education system along with the widespread idea of ​​Islamic reform throughout the 18th and 19th centuries.